Tang Huat Restaurant Online Food Ordering System - YANG, JENG FOONG; Mohd Zainuri Saringat (Applied Information Technology And Computer Science, 2024)
Online Food ordering system is a web-based system that allows the consumer to order food from the Internet using a web browser. TANG HUAT RESTAURANT is a food-selling business that sells a variety of food using WhatsApp and Telegram. The problems faced by the owner are difficulty tracking back orders, the need to calculate the monthly sales manually and not having a proper online menu. The objective of this system is to design an online food ordering system using an object-oriented approach, to develop the system and to test system. The system was developed based on the Iterative methodology. The system was launched on the web server and live on the Internet so that the customer can order food using their web browser. This system is expected to help customers to save time when ordering food and owner or staff to manage customers’ orders efficiently.